Fusarium species, chemotype characterisation and trichothecene contamination of durum and soft wheat in an area of central Italy - Covarelli, Lorenzo; Beccari, G.; Prodi, A.; Generotti, S.; Etruschi, F.; Juan, C.; Ferrer, E.; Mañes, J. (John Wiley and Sons Inc., 2015)
© 2014 Society of Chemical Industry. BACKGROUND: Fusarium head blight (FHB) of wheat is an important disease causing yield losses and mycotoxin contamination. The aim of the work was to detect and characterise trichothecene producing Fusarium species in durum and soft wheat cultivated in an area of central Italy in 2009 and 2010 and to determine trichothecene contamination by LC-MS/MS in the grain. RESULTS: F. graminearum s. str. was the most frequent species. In 2009, the occurrence of F. avenaceum and F. poae was higher than in 2010. Among F. graminearum strains, the 15-acetyl deoxynivalenol (15-ADON) chemotype could be found more frequently, followed by nivalenol (NIV) and 3-ADON chemotypes, while all F. culmorum isolates belonged to the 3-ADON chemotype. All F. poae strains were NIV chemotypes. In vitro trichothecene production confirmed molecular characterisation. Durum wheat was characterised by a higher average DON contamination with respect to soft wheat, NIV was always detected at appreciable levels while type-A trichothecenes were mostly found in durum wheat samples in 2009 with 6% of samples exceeding the contamination level recently recommended by the European Union. CONCLUSION: Climatic conditions were confirmed to be predominant factors influencing mycotoxigenic species composition and mycotoxin contaminations. However, NIV contamination was found to occur irrespective of climatic conditions, suggesting that it may often represent an under-estimated risk to be further investigated.